УСТУПИТЕЛЬНОЕ НАКЛОНЕНИЕ В БУРЯТСКОМ ЯЗЫКЕ : (К ПОСТАНОВКЕ ВОПРОСА) - Бадмацыренова Н.Б (Acta Mongolica, 2013)
Though, although under the category of general linguistics treated fairly unique. As a rule, the proposals expressing concessive relations , the two situations are related . In this case, one of them made an unfavorable condition , circumstance preventing another situation . Perhaps such a relationship when one situation contains an amendment that limits the lie are absolute that is approved in another situation . Operation of verb forms in the Mongolian languages that make up the paradigm of concessive mood in particular, and the allocation of concessive mood in general , have not received a satisfactory lighting in research on modern Mongolian languages. Though, although the question of the mood in these languages requires careful analysis and detailed consideration in terms of values and meanings transmitted.